The Impact of Sustainable Forest Management and Environmental Regulation Enforcement on Reducing Deforestation Rates in Indonesia - Olivia Marie Caesaria Kesauliya; Christian Soleman Imburi; Novaldi Laudi Angrianto; Evelin Anggelina Tanur (Westscience Press, 2026)
This study aims to analyze the impact of sustainable forest management and environmental regulation enforcement on reducing deforestation rates in Indonesia. A quantitative approach was employed using primary data collected from 85 respondents through a structured questionnaire based on a Likert scale. The data were processed and analyzed using IBM SPSS Statistics 25, including validity, reliability, classical assumption tests, and multiple linear regression analysis. The results show that sustainable forest management has a significant positive effect on deforestation reduction, while environmental regulation enforcement also has a significant positive effect. Simultaneously, both variables significantly influence deforestation reduction, with a coefficient of determination (R²) of 0.511, indicating that 51.1% of the variation in deforestation reduction can be explained by the model. These findings highlight that the integration of effective forest management practices and strong regulatory enforcement plays a crucial role in mitigating deforestation. This study provides empirical evidence to support policymakers in strengthening sustainable environmental governance strategies in Indonesia.